A guide to Monte Carlo simulation concepts for assessment of risk-return profiles for regulatory purposes - Stefan Graf; Ralf Korn (European Actuarial Journal, 2020)
Various regulatory initiatives (such as the pan-European PRIIP-regulation or the German chance-risk classification for state subsidized pension products) have been introduced that require product providers to assess and disclose the risk-return profile of their issued products by means of a key information document. We will in this context outline a concept for a (forward-looking) simulation-based approach and highlight its application and advantages. For reasons of comparison, we further illustrate the performance of approximation methods based on a projection of observed returns into the future such as the Cornish–Fisher expansion or bootstrap methods.
Keywords: 510; Risk-return profiles of pension products; Customer protection; Regulatory requirements